A case study of the role of leadership behaviour in the formation of organizational culture - Moore, Aminah (Rhodes University, Faculty of Commerce, Rhodes Business School, 2018)
This case study research on the effect of leadership on organizational culture, is based on a small luxury tourism organization "“ Belmond Safaris "“ based in Maun, Botswana. The study set out to determine critical incidents that occurred during the tenure of the current general manager with the intention of uncovering her leadership behaviour and how it has shaped the culture of the organization. The literature review identified quantitative and qualitative approaches to researching organizational culture, but settles on Schein's theory of organizational culture (Schein, 1992; 2010) as the approach adopted in this study. Furthermore, it reviews the various roles of strategic leaders and how these affect the culture of the organization. The study follows a qualitative methodology and applies the Critical Incident Technique to explore how, as a leader, the behaviour of the general manager shaped the organization's culture. Data triangulation is achieved through the use of multiple sources "“ interviews, analysis of company documents and the examination of minutes of management meetings. Following the fieldwork, the evidence within the findings of the study required a theoretical reorientation and a shift from strategic leadership to a new focus on relational leadership, highlighting the prominence of social exchanges between the general manager and employees, as opposed to economic exchanges. The study concludes by acknowledging the limitations and delimitations of the study, which include time constraints as well as the deliberate exclusion of certain participants (e.g. camp managers) from the study. In its conclusion the study also presents recommendations for future studies. The researcher recommends a broader study within the tourism industry, as well as a larger and more inclusive sample size, in order to obtain better insights into the study of culture and leadership within organizations.
Keywords: Leadership -- Botswana -- Maun; Corporate culture -- Botswana -- Maun; Strategic planning -- Botswana -- Maun; Critical incident technique; Organizational behavior -- Botswana -- Maun; Tourism -- Management; Belmond Safaris (Botswana)